Legal Politics Formation of Law Concerning Law Number 9 of 2009 Educational Legal Entities - Irmanjaya Thaher (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The research objective is to examine the process of forming the BHP bill in the DPR RI until the ratification of the bill becomes law. analyze the decisions of Constitutional Court Numbers 11-14-21-126 and 136/PUU-VII/2009 NUMBER 11-14-21-126 and 136/PUU-VII/2009 regarding the cancellation of the BHP law. The legal research methods used in this research are normative research methods and empirical legal methods. Normative legal research methods use primary legal materials, secondary legal materials, and tertiary legal materials. Conclusion Based on the BHP Bill which was passed as law number 9 of 2009 concerning Education Legal Entities, the community submitted a judicial review of the BHP law to the Constitutional Court. Based on the fact that the Constitutional Court annulled the BHP law in its entirety because it was deemed contrary to Article 28 D of the 1945 Constitution and Article 31 paragraph (1). The implication is that all tertiary institutions and education practitioners who have implemented the BHP system must change the system back to become state universities so that academic staff and lecturers who were appointed when using the BHP system requested that they be appointed as civil servants. The community and foundation managers are not affected by the negative effects of BHP